Reviewing the SEC's Review Process: 10-K Comment Letters and the Cost of Remediation - Cassell, Cory A.; Dreher, Lauren M.; Myers, Linda A. (The Accounting Review, 2013)
ABSTRACT: Securities and Exchange Commission (SEC) comment letters provide independent and timely feedback on the clarity of disclosures and on the extent to which filings comply with Generally Accepted Accounting Principles and SEC reporting regulations. We investigate factors that affect the probability of receiving a 10-K comment letter, the extent of comments received, and the cost of remediation. We find that in addition to factors explicitly stated to increase SEC scrutiny in Section 408 of the Sarbanes-Oxley Act, low profitability, high complexity, engaging a small audit firm, and weaknesses in governance are positively associated with the receipt of a comment letter, the extent of comments, and the cost of remediation. The probability that the comment letter results in a restatement is higher for smaller companies and for companies engaging a small audit firm. We also provide evidence that comments relating to accounting issues result in higher remediation costs, largely due to the additional time required to resolve comments relating to classification issues and fair value issues. Our findings should be of interest to stakeholders who use SEC comment letters to assess disclosure quality and reporting compliance, and to managers and other stakeholders impacted by costs associated with the SEC's review process. Data Availability All data used in the study are publicly available from the sources cited in the text.